Microgravity's effects on miRNA-mRNA regulatory networks in a mouse model of segmental bone defects. - Aarti Gautam; Nabarun Chakraborty; George Dimitrov; Allison Hoke; Stacy Ann Miller; Kevin Swift; Bintu Sowe; Carolynn Conley; Melissa A Kacena; Rasha Hammamieh (PLoS ONE)
Rehabilitation from musculoskeletal injuries (MSKI) complicate healing dynamics typically by sustained disuse of bone and muscles. Microgravity naturally allows limb disuse and thus an effective model to understand MSKI. The current study examined epigenetic changes in a segmental bone defect (SBD) mouse model in a prolonged unloading condition after spaceflight (FLT). We further connected potential miRNA-mRNA regulatory pathways impacting bone healing. Here, SBD surgery was performed on nine-week-old male mice that were launched into space for approximately 4 weeks. Sham with no surgery and ground controls were included in the study. The midshaft of the ipsilateral femur (with callus on the surgical mice) as well as the ipsilateral quadriceps tissue were used for analysis. Femur and quadriceps had a distinct miRNA profile. There was a stronger surgery effect as observed by miRNA expression when compared to microgravity effects. Leukopoiesis, granulopoiesis, myelopoiesis of leukocytes, differentiation of myeloid leukocytes, and differentiation of progenitor cells were all altered because of surgery in the femur. The biological functions such as apoptosis, necrosis, and activation of cell migration and viability were altered because of surgery in quadriceps. Integrating the transcriptome and microRNA data indicated pronounced changes because of microgravity. According to pathway analysis, microgravity had a greater impact on the quadriceps tissue than the bone tissue in the absence of surgery. The altered biological functions resulting from microgravity were validated by integrating limited proteomics data to miRNA-mRNA. Thus, this study highlights the importance of dynamic interplay of gene-epigene regulations as they appear to be intrinsically interconnected and influence in combination for the biological outcome.